Concussion injuries in sports and the role of instrumented mouthguards: a mini review - Chilmeran, Zaid; Akhtar, Muhammad Umair; Sharafeldin, Abu-Baker Khalid; Gaynor, Declan (Frontiers in Bioengineering and Biotechnology, 2025)
Contact sports such as American football, rugby, soccer, and ice hockey involve high-speed, high-impact interactions that frequently result in head acceleration events (HAEs), which can lead to concussions and other forms of traumatic brain injury. HAEs can lead to acute symptoms like dizziness and memory difficulties, as well as more severe, chronic conditions like cognitive decline and chronic traumatic encephalopathy. This mini-review focuses on concussion-related injuries in contact sports, examining their prevalence, impact, and the role of innovative prevention strategies. Particular attention is given to the development of instrumented mouthguards (iMGs), which incorporate real-time sensors to measure and analyze head impacts. Ultimately, this review aims to provide an overview of the role of iMGs on concussion prevention and its evolving landscape, with a focus on the potential of iMG technology.